48.7k views
1 vote
Evaluate 3xy- y + 6z when x = 1, y = - 2 and z = 3

User Subbu
by
4.8k points

2 Answers

4 votes

Answer:

14

Explanation:


3xy- y + 6z \\\\x = 1\\ y = - 2 \\ z = 3\\\\3(1)(-2) - (-2) +6(3)\\-6 + 2 +18\\=14

User Damote
by
4.6k points
3 votes

Answer:


\boxed{ \bold{ \huge{ \boxed{ \sf{14}}}}}

Explanation:

Given, x = 1 , y = -2 , z = 3


\sf{3xy - y + 6z}

Plug the value of x , y and z


\sf{3 * 1 * ( - 2) - ( - 2) + 6 * 3}

Multiply the numbers


\sf{ - 6 - ( - 2) + 6 * 3}

We know that ,
\sf{( - ) * ( - ) = ( + )}


\sf{ - 6 + 2 + 6 * 3}

Multiply the numbers : 6 and 3


\sf{ - 6 + 2 + 18}

Add the numbers : 2 and 18


\sf{ - 6 + 20}

Calculate the difference


\sf{14}

Hope I helped !

Best regards!!

User David Titarenco
by
4.9k points